People’s Voices on the Sustainable Forest Reform in the Democratic Republic of Congo - Filomena Amaral; João Simão (Modern Africa)
Since the early 2000s, the Democratic Republic of Congo has been conducting a reform of its forestry sector with the publication of The Forest Code (2002). The implementation of this law, which aims to assure the participation of all stakeholders, has been evolving slowly since then. The present research aims to evaluate the knowledge local communities and indigenous people detain over the ongoing reform, and the expectations they created when negotiations over the implementation of industrial harvesting activities in their traditional territories began. By interviewing local people, we came to understand that insufficient knowledge regarding the law gathers with a lack of concern towards ecological or environmental matters and with the need of seeing basic needs satisfied; all this in a context in which different stakeholders’ responsibilities and negotiational terms are often misunderstood.